Effects of Allopurinol on Ketone Body Metabolism and Tissue Lipid Peroxidation in Alloxan Diabetes in Rats. - Saleh A. Wohaieb (College of Pharmacy University of Baghdad, 2017)
The aim of the present study is to investigate whether or not xanthine oxidase (XO)â€"derived reactive oxygen species (ROS) may play a role in the pathogenesis of alloxan (ALX)â€"induced diabetes in rats using the specific XO inhibitor and hydroxyl radical scavenger, allopurinol The involvement of oxidative stress in ALX â€" diabetes was assessed by the measurement of plasma and various tissues lipid peroxides levels ( using thiobarbituric acid ( TBA ) reactive substances ). Furthermore, the ability of allopurinol to influence these and other biochemical parameters, including plasma and urine ketones levels were also investigated in diabetic rats. Rats were divided into four groups: control, untreated diabetic, allopurinol â€" treated diabetic, and insulin â€" treated diabetics. At the end of the one week experimental period, blood and tissue samples were obtained from anesthesized animals for the measurement of the above â€" mentioned parameters.    Although the single intraperitoneal (i.p.) injection of allopurinol (25 mg/kg body wt.) 1h before or 1h after ALX injection (100 mg/kg body wt., i.p.) failed to prevent the induction of diabetes, it did lower ketonuria and the incidence of early ketosisâ€"associated mortality in diabetic animals in comparison with nonâ€"allopurinolâ€"treated diabetic rats. Subsequent administration of allopurinol (25 mg/kg body wt., i.p.) every 48 hr for 1wk (i.e., 3 additional doses) also decreased plasma ketone bodies levels as well as plasma and tissue (heart, liver, kidney, pancreas) lipid peroxides levels in comparison with nonâ€"allopurinolâ€"treated diabetic rats. Daily insulin injection (9â€"12 U/kg body wt., S.C.) for 1wk period normalized all of the aboveâ€"mentioned abnormalities. The present results suggest that XOâ€"derived ROS play a minor role (if any) in the diabetogenic effect of ALX. On the other hand, although the mechanism (s) underlying the protective effects of allopurinol on the diabetic state is presently unknown, these effects may reflect a possible association between impaired ketone body metabolism and lipid peroxidation: and suggest an effect of allopurinol on ketone body metabolism.